Between Violence, Vulnerability, Resilience and Resistance Arab Television News on the Experiences of Syrian Women during the Syrian Conflict - El Zein, Rand (Critical Studies in Media and Communication, 2021)
How are the structures of power and the notion of agency among Syrian women during the recent Syrian conflict connected? To explore this matter, Rand El Zein investigates gender politics around displacement, conflict, the body, and the nation. In doing so, she outstandingly reconciles critical media theory as myriad and productive with the theoretical concepts on subjectivity, power, performativity, neoliberalism, and humanitarian governance. The book examines how the Arab television news discursively represented the experiences of Syrian women during the conflict in relation to the four main concepts: violence, vulnerability, resilience, and resistance.